L’utopie chez Houellebecq : interprétation des éléments dominants et du style d’écriture dans l’univers houellebecquien - Hua Hu (ReS Futurae)
In Houellebecq’s work, whether the element is the alienated society empowered by money, market and information technology or human beings disturbed by the materialization of their “Corps”, “Utopia” is always the major theme that bonds all those elements. The study tries to take “Utopia” as a principle line to systematically analyze the themes, literary creation styles and other related elements in Houellebecq’s work from three aspects. First, we investigated the origin of “Utopia” in Houellebecq’s work ; and then we examined how “Utopia” is presented in his work ; At last, we studied how the vitality of “Utopia” is constructed in Houellebecq’s work. As far as the content is concerned, the “Utopia” in Houellebecq’s work is based on technology techniques, literature creations and “sex”. As for the form, “Utopia” is the future city created by Houellebecq, which transcends time and space. “Utopia” and “dystopia” together construct Houellebecq’s narrative discourse. Houellebecq who has dual personality is good at making use of irony and contradictions, which results in a sense of ambiguity and tension in his work and further more, makes “Utopia” full of mysteries.